KNOWLEDGE AND PERCEPTION TOWARDS PHARMACOVIGILANCE AND ADVERSE DRUG REPORTING AMONG PHARMACY AND NURSING STUDENTS IN AL JOUF UNIVERSITY: Pharmaceutical Science-Pharmacovigilance - MAGABLEH, ODAI; ALHAMED, GHAIDA (International Journal of Life Science and Pharma Research, 2019)
Pharmacovigilance is one of the building blocks of health education in the community, which includes prevention of side effects of drugs or their complications caused by either the misuse of the dosage during the treatment period or the frequent use without medical consultation. Many international bodies and organizations, including the World Health Organization (WHO), are interested in this concept, formulating it on the basis of scientific basis for reporting, evaluation, prevention and early detection of drug side effects. The aim of this study was to determine the level of ADR’s Knowledge and Perceptions of Pharmacovigilance and adverse drug reactions (ADRs) reporting between pharmacy students and medical students of Aljouf university. This is descriptive cross-sectional surveys which determine the Knowledge and Perceptions of Pharmacovigilance of pharmacy students and medical students of Aljouf University that was conducted from March - April 2017. Design of a structured questionnaire was administered as regards pharmacovigilance and ADRs reporting process. The mean knowledge score of pharmacovigilance and ADR reporting for the overall study sample was 2.99 (SD=0.44) with a scoring range from 0 to 9. Findings of the current study had demonstrated that there is insufficient knowledge level among pharmacy and nursing students regarding pharmacovigilance and ADRs reporting systems. Investigating the pharmacy and nursing students’ perceptions toward ADRs reporting had demonstrated that they are having positive perceptions about reporting ADRs. Study concluded that there is insufficient knowledge level among pharmacy and nursing students regarding pharmacovigilance and ADRs reporting systems and a positive perception towards ADRs. Study recommends the necessity of an educational intervention plan that aims to increase the undergraduate healthcare workers knowledge and perceptions towards pharmacovigilance and ADRs reporting system.